Treatment of acute pulmonary embolism with dabigatran versus warfarin - Goldhaber, Samuel Zachary; Feuring, Martin (Thrombosis and haemostasis, 2016)
Dabigatran was non-inferior to warfarin for prevention of recurrent venous thromboembolism (VTE), and dabigatran had a lower rate of bleeding compared with warfarin in two large-scale randomised trials, RE-COVER and RE-COVER II. In this study, we investigate the efficacy and safety of dabigatran versus warfarin according to the index event that qualified the patient for enrollment, either symptomatic pulmonary embolism (PE) with or without deep-vein thrombosis (DVT), or DVT alone. We then analyse the anticoagulant effect of dabigatran vs warfarin on patients enrolled with PE. The pooled dataset for the efficacy analysis consisted of 2553 and 2554 patients who were randomised to dabigatran and warfarin, respectively. Recurrent VTE/VTE-related death during the study period and additional 30-day follow-up occurred in 2.7 % of all patients on dabigatran and in 2.4 % on warfarin (hazard ratio [HR] 1.09 [95 % confidence interval 0.77, 1.54]). In patients with PE as their index event, recurrent VTE/VTE-related death occurred in 2.9 % vs 3.1 % of patients (HR 0.93 [0.53, 1.64]). There were significantly fewer major bleeding events in patients treated with dabigatran than with warfarin (HR 0.60 [0.36, 0.99]). The pattern was similar both in patients with PE and in those with DVT alone as the index event. These analyses of the pooled dataset from the RECOVER and RE-COVER II trials indicate that dabigatran is as effective as warfarin in preventing recurrent VTE, regardless of whether patients present with symptomatic PE (with or without DVT) or with symptomatic DVT alone. Dabigatran was also associated with a lower risk of bleeding than warfarin, regardless of the index event.